Acute swimming stress induces changes in noradrenergic mechanisms in order to maintain the response pattern of the rat vas deferens to norepinephrine - Sanchez, A.; Pereira, OCM (Elsevier B.V., 2002)
This study investigated mechanisms involved in the maintenance of the functional response pattern of the postjunctional alpha(1)-adrenoceptor in vas deferens isolated from rats submitted to acute swimming stress. The plasma corticosterone levels increased approximately three times after the swimming stress in the nontreated rats as well as after swimming stress in the rats pretreated with desipramine (DMI), yohimbine (YO), or DMI with YO. No alteration was detected in the sensitivity to norepinephrine (NE) in the vasa deferentia from the stressed rats or stressed rats treated with DMI or DMI with YO, in relation to their respective control. However, when the vasa deferentia were previously incubated with DMI, a reduction in sensitivity to NE in organs from stressed rats was observed. Vasa deferentia excised from rats pretreated with YO before the swimming stress showed an increase in postjunctional alpha(1)-response that was abolished by prazosin (PZ). Thus, the neuronal uptake, the prejunctional alpha(2)-adrenoceptors (mediating prejunctional inhibition), the occupancy and functional response of the postjunctional alpha(1)-adrenoceptors, and the emotional stress component were very important for the determination of the noradrenergic response pattern in vas deferens from rats submitted to acute swimming stress. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: swimming stress; norepinephrine; corticosterone; desipramine; yohimbine; vas deferens; rat